P3-S7.10 Composition of vaginal microbiota in bacterial vaginosis patients and healthy women: basis for genetic diagnosis of bacterial vaginosis?. (10th July 2011) - Unemo, M; Fahlen, A; Datcu, R; Hallen, A; Fredlund, H; Jensen, J; Engstrand, L
Abstract : Background: Bacterial vaginosis (BV) is the most common vaginal infection/disorder. BV is characterised by imbalance in the normal vaginal microbiota with a shift towards higher bacterial diversity and increased pH. The aim of the present study was to describe the differences in vaginal microbiota composition in women suffering from BV compared to healthy women, using massive parallel 454 pyrosequencing. Methods: 163 vaginal samples were collected from women diagnosed with characteristic BV (n=73), women with intermediate BV (n=11), and from healthy women on their regular check-ups (n=79). DNA from the samples was isolated and the bacterial compositions as well as the relative abundance of these bacteria were analysed using 454 pyrosequencing, with GS Titanium amplicons kit (Roche Inc.), of the hypervariable region V4 on the 16S rRNA gene. Finally, 17 different species-specific PCRs were used to verify the species of bacteria found in the 454 pyrosequencing. Results: Extensive imbalance of the vaginal microbiota of women with BV compared to healthy controls was revealed. The dominating taxons of the 73 BV cases were Gardnerella, Atopobium, Prevotella, Lactobacillus, Megasphera and Sneathia, while most of the 79 healthy controls had a microbiota totally dominated by Lactobacillus with the BV associated taxons hardly detectable. Furthermore, the 11 patients with intermediate BV predominantly had a mix of the BV associated taxon Gardnerella as well as Lactobacillus. A few of the healthy controls seemed to have a microbiota changing towards the intermediate microflora. Gardnerella may be the first bacteria to establish in the transition from healthy vaginal flora towards a BV associated flora. Conclusions: A clear difference in the composition of the vaginal microbiota between individuals suffering from BV and healthy controls was identified. The present findings are important steps towards the determination of valid potential bacterial markers for BV, are shedding light upon why some women develop BV, as well as show how the microbiota is involved in the development of BV. Knowledge of the composition of the vaginal microbiota is crucial in the development of a BV diagnostic tool and for elucidating appropriate treatment for use in clinical practice.